A transdisciplinaridade no encino superior em Cabo Verde - Jorge Brito Sousa (EccoS – Revista Científica)
Historical and geographic reasons transformed Cape Verde, across the last five centuries, into a place of civilizations´ confluence and experimentation / acclimatization of the most diverse resources and ideas. This was expressed as an open society to the world, an economy of circulation and through the universal personality of the Capeverdian man. This strategic position in a globalized world requires a transdisciplinary vision from the citizen. Higher education is a privileged vehicle for such an end and under the scope of UNESCO´s recommendations transdisciplinarity must be part of the new 21st century university. The birth of a transdisciplinary university in Cape Verde looks like a natural thing. Such university was born in 2001(University Jean Piaget of Cape Verde) and already develops a transdisciplinary action and research pointed in this direction. However, Cape Verde´s context of higher education lacks of bigger attention and the transdisciplinary vision would be more than necessary for a liberal education, for the benefit of a terrestrial citizenship